As Barreiras como instrumento econômico para o desenvolvimento da rede viária da Província de São Paulo (1835-1850) - José Rogério Beier (Confins)
This paper takes the “Barriers” of the São Paulo Province as the main study object in order to analyze the role played by this fiscal posts in the development of the São Paulo road network between 1835, when the first Barreiras were installed, and 1850, when the coffee production definitively assumes the prominence, not only in terms of exported values, but also in exportation volume, demanding structural changes in the São Paulo transportation network, such as the installation of the railroads, aiming to reduce the costs of the production transportation to the port of Santos.